The comparison of preliminary structure and intestinal anti-inflammatory and anti-oxidative activities of polysaccharides from different root parts of Angelica sinensis (Oliv.) Diels. (15th September 2022) - Zou, Yuan-Feng; Li, Cen-Yu; Fu, Yu-Ping; Jiang, Quan-Xing; Peng, Xi; Li, Li-Xia; Song, Xu; Zhao, Xing-Hong; Li, Yang-Ping; Chen, Xing-Fu; Feng, Bing; Huang, Chao; et al.
Abstract: Ethnopharmacological relevance: The root of Angelica sinensis, has been commonly used in gynecology for centuries, and is normally applied divided into different parts in various clinical applications. At present, the majority of existing studies focus on the volatile oil and ferulic acid extracted from different parts of A. sinensis, but there is a dearth of scientific information on its water-soluble polysaccharides. Aim of the study: The structures of polysaccharides from plants, have been reported contributing to multiple pharmacological activities such as anti-oxidative, anti-inflammatory, anti-tumor and liver protection. Therefore, the focus of this study was on its anti-oxidative and anti-inflammatory activities in vitro, which would be based on the various polysaccharides with distinct structures obtained from different parts of the A. sinensis root. Materials and methods: Four parts of A. sinensis root were separated according to the Chinese Pharmacopoeia: head, body, tail and whole body. Crude polysaccharides were obtained by water extraction and ethanol precipitation method, and were further fractionated by DEAE Sepharose chromatographic column and gel filtration. The comparison of ASPs from different root parts were performed, including chemical compositions determined by colorimetric analysis, monosaccharide compositions measured by high performance liquid chromatography (HPLC), glycosidic linkage units determined by methylation and gas chromatography-mass spectrometry (GC-MS), organic functional groups determined by FT-IR, molecular weight ( Mw ) demarcated by gel permeation chromatography, and the viscosities and solubilities were measured according to method published in the previous report with minor modification. In vitro biological activities of APSs were compared on lipopolysaccharide (LPS)-induced inflammatory and oxidative stress models on IPEC-J2 cells. Results: Four purified polysaccharides, ASP-H-AP, ASP-B-AP, ASP-T-AP and ASP-Hb-AP from the root of A. sinensis, were obtained, and consisted of various contents of protein and the polyphenol. They were possibly pectic polysaccharides with a long homogalacturonan region as the main backbone and ramified with rhamnogalacturonan I region, but they were differed by subregions and the relative contents of glycosidic units. The Mw of four pectic polysaccharides were ranged from 67.9–267.7 kDa. The infrared spectrum also showed that the four polysaccharide fractions contained the characteristic peaks of polysaccharides. Their distinct primary structure could lead to a variety of biological activities. In vitro biological assays suggested that four polysaccharide fractions can protect IPEC-J2 cells against the LPS-induced inflammation by down-regulating inflammation factors and related genes on IPEC-J2 cells. These polysaccharides also could alleviate oxidative stress on IPEC-J2 cells by up-regulating the gene and protein expressions of antioxidant enzymes. It was concluded that ASP-H-AP possessed better anti-inflammatory and anti-oxidative effects, while those of ASP-T-AP was relatively poor among the four polysaccharide fractions. Conclusion: All results indicated that the structure of pectic polysaccharides from different root parts of A. sinensis differed, which lead to their distinct anti-inflammatory and anti-oxidative activities. This may also be one of the factors why different parts of A. sinensis showed various pharmacological activities and applied independently in traditional use. In addition, it would be valuable for further studies on structure-activity relationship of polysaccharides obtained by different root parts of A. sinensis . Graphical abstract: Image 1